Report on capacity building in scaling on Systems of Rice intensification (SRI) to produce more rice with less water - Suh, Neville N; Diawara, Bandiougou; Dossou-Yovo, Elliott (2024)
Organizing capacity-building training workshops can help to address climate change impacts and risks in Mali's rice-based systems, which is imperative for achieving sustainable and resilient livelihoods for rice farmers. This report presents activities carried out on 20th November 2024 during the capacity-building workshop organized by the AICCRA Mali team for the effective deployment of climate-smart technologies and climate information services in rice-based systems in Mali. The one-day training session on Systems of Rice Intensification (SRI) was attended by 29 participants, including 4 females, from 13 different organizations in Mali. Participants gained insightful knowledge of the different SRI practices and the 6 principles of SRI. The benefits of SRI were also outlined, with yield increase and reduced quantity of inputs being some of the most important benefits. Participants were encouraged to disseminate the knowledge and information gained during the training with other actors participating in rice value chain activities in Sikasso, Segou, Koulikoro regions, and beyond.